1995
DOI: 10.1177/036354659502300521
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation: Effects on Biomechanical Properties of Human Bone-Patellar Tendon-Bone Allografts

Abstract: Sixty 10-mm bone-patellar tendon-bone allografts from young human donors were placed into four test groups, a control fresh-frozen group and three fresh-frozen irradiated groups. The irradiated groups were exposed to 2.0, 3.0, or 4.0 Mrad of gamma irradiation. The specimens were tested to tensile failure. The initial biomechanical strength of fresh-frozen allografts was reduced up to 15% when compared with fresh-frozen controls after 2.0 Mrad of irradiation. Maximum force, strain energy, modulus, and maximum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
192
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(205 citation statements)
references
References 26 publications
7
192
1
5
Order By: Relevance
“…3a). These observations are consistent with reports [6,[8][9][10]12,13,19] of the significant effect of gamma irradiation on the plastic properties such as the bending strength and toughness, rather than the elastic properties such as stiffness and elastic limit. Of importance is that although the irradiation doses in question are very large compared to the few second exposures typical of in situ x-ray scattering experiments, they are definitely comparable to the irradiation associated typical tomography imaging runs (Table 1),…”
Section: Strength and Fracture Toughnesssupporting
confidence: 92%
See 1 more Smart Citation
“…3a). These observations are consistent with reports [6,[8][9][10]12,13,19] of the significant effect of gamma irradiation on the plastic properties such as the bending strength and toughness, rather than the elastic properties such as stiffness and elastic limit. Of importance is that although the irradiation doses in question are very large compared to the few second exposures typical of in situ x-ray scattering experiments, they are definitely comparable to the irradiation associated typical tomography imaging runs (Table 1),…”
Section: Strength and Fracture Toughnesssupporting
confidence: 92%
“…At the high dose end (>10 kGy), gamma irradiation is commonly used to terminally sterilize allograft tissues and bones [2][3][4][5], and has been proven to be very potent sterilization agent with the ability to effectively penetrate tissue. However, gamma irradiation is also known to adversely affect the mechanical and biological properties of tissue in a dose-dependent manner by degrading the collagen [6][7][8][9][10][11][12][13][14]. Specifically, gamma rays split polypeptide chains; in wet specimens, irradiation causes release of free radicals via radiolysis of water molecules that induces cross-linking reactions in collagen molecules [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies (Fideler et al, 1995;Curran et al, 2004) have shown that gamma irradiation has adverse effects on biomechanical properties of allograft in a dose-dependent manner. Fideler et al (1995) demonstrated a dose-dependent effect of irradiation on both the structural and mechanical properties of human BPTB allograft.…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies (Fideler et al, 1995;Curran et al, 2004;Schwartz et al, 2006;Grieb et al, 2006;Balsly et al, 2008) have shown that gamma irradiation significantly alters the initial biomechanical properties of allografts in a dose-dependent manner. A dose as low as 2.5 mrad commonly used by tissue banks has been shown to reduce the initial stiffness and strength of tendon allografts.…”
Section: Introductionmentioning
confidence: 99%
“…This risk can be minimized by using various sterilizing methods. However, these methods are complex, expensive and damage the osteogenic properties of the allograft (Ijiri et al 1994, Fideler et al 1995, Thoren and Aspenberg 1995, Currey et al 1997, Aspenberg and Lindqvist 1998, Boyce et al 1999). In our previous study, we found pulse lavage washing very effective in reducing bacterial contamination of the allograft bone (Hirn et al 2001).…”
mentioning
confidence: 99%